Co-cultivation of microalgae in aquaponic systems. (December 2017) - Addy, Min M.; Kabir, Faryal; Zhang, Renchuan; Lu, Qian; Deng, Xiangyuan; Current, Dean; Griffith, Richard; Ma, Yiwei; Zhou, Wenguang; Chen, Paul; Ruan, Roger
Highlights: Algae production was tested at 4.15 g/m 2 ·day. The algae help balancing the pH drop in aquaponic systems. The algae help controlling the ammonia level. The algae are unlikely to compete with vegetable for nitrate usage but improve the overall nitrogen removal efficiency. Abstract: Aquaponics is a sustainable system for the future farming. In aquaponic systems, the nutrient-rich wastewater generated by the fish provides nutrients needed for vegetable growth. In the present study, the role of microalgae of Chlorella sp. in the floating-raft aquaponic system was evaluated for ammonia control. The yields of algal biomass, vegetable, and removal of the key nutrients from the systems were monitored during the operation of the aquaponic systems. When the systems were in full operation, the algae production was about 4.15 ± 0.19 g/m 2 ·day (dry basis) which is considered low because the growth conditions are primarily tailored to fish and vegetable production. However, it was found that algae had a positive effect on balancing pH drop caused by nitrifying bacteria, and the ammonia could be controlled by algae since algae prefer for ammonia nitrogen over nitrate nitrogen. The algae are more efficient for overall nitrogen removal than vegetables.